Newspaper article on the steamship Savannah - Savannah (Steamship)
Article (May 1934) in the Cheraw Chronicle, Cheraw, S.C., concerning the voyage (1819) of the Savannah, the first transatlantic voyage of a steamship, under the command of Captain Moses Rogers.
Handwritten transcript.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Rogers, Moses, -- 1779-1821.; Steamboats; Transatlantic voyages